Avaliação do desempenho logístico-operacional de empresas no setor da floricultura: um estudo de caso no Ceará - Tomé, Luciana Mota (2004)
The importance of flower cultivation has been increasing in the State of Ceará (in the Northeastern Brazil) Economy since the end of the last decade, when it was clear the great potential to produce flowers for export in Mount Ibiapaba. Since then, many enterprises has been operating in that region as is the case of CeaRosa, the first to operate and nowadays supplying a significant part of the national market, as well as Reijers, the biggest national flower producerand presently in the pole position of the Ceará State flower culture export sector. Flower culture enterprises in Northeastern Brazil normally utilize advanced techniques in agriculture production, according to the best national and international practices in the sector. Nevertheless, logistics problems that can make difficult flower culture enterprise sustainability can be easily found and those difficulties need to be overcome. This MSc Dissertation presents a methodology to evaluate flower culture supply chain performance – the ADEFLO Methodology, which is based in benchmarking techniques. It can be used both to let to know the very efficacy of flower culture enterprise logistics operations and to encourage the enterprise to create a data base on the sector it is involved. A case study was developed to apply the methodology using CeaRosa as an enterprise to be evaluated and Reijers as the benchmark enterprise. The results show a diagnosis not only ofthe CeaRosa Enterprise but also of the flower culture sector in the State of Ceará, making possible to propose solutions to the problems found out.